Enhancing the applicability of Al-Mg compounds by using forming and welding technologies. (2017) - Förster, W; Habisch, S.; Binotsch, C.; Awiszus, B.; Mayr, P.
Abstract: The role of oxide layers in the formation of a sufficient bonding between aluminum (Al) and magnesium (Mg) as a compound is essential, due to their impediment of the diffusion process. For this investigation into the formability and weldability of such compounds, specimens with an Mg core and an Al cladding were prepared by chemically removing the oxide layers. The specimens were joined mechanically in an inert atmosphere and then forged at 400°C. The bonding quality was investigated by optical microscopy and compared to co-extruded specimens. It was shown that a complete interface between the materials was formed. Furthermore, FE simulation was used for the investigation into the material flow during the forging process and for a comparison with the co-extruded specimens. For the welding experiments, a unique concept for in-line surface treatment and diffusion bonding was used to treat and transfer specimens under inert atmosphere into a diffusion bonding chamber, thereby improving the diffusivity, especially at lower temperatures. The results showed, that the bonding temperature was decreased to almost the forging temperature, while the interface of the diffusion-bonded Al-Mg compounds exhibited nearly no imperfections. Furthermore, no significant increase in hardness was measured at the interface.